Analisis Konvergensi IFRS dan Manajemen Laba: Tinjauan Literatur terhadap Pengaruhnya di Indonesia dalam Kerangka Konseptual Akuntansi - Murdoko, Berta Dwi (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to explore the influence of IFRS convergence on earnings management through a literature review. Converged International Financial Reporting Standards (IFRS) is an important step taken by Indonesia to increase transparency and comparability of financial reports. Studies show that IFRS convergence tends to tighten oversight of accounting practices, which can reduce the scope for management to manipulate earnings. However, even though IFRS is designed to increase transparency, earnings management practices can still increase due to pressure to meet market expectations. Through this analysis, it is hoped that readers can understand the dynamics between IFRS convergence and earnings management, as well as the influence on stakeholders such as investors and accounting practitioners. This article contributes to the understanding of the effects of IFRS convergence in Indonesia and recommends further research on the influence of international accounting standards in further developing countries. Keywords: Earnings Management, Financial Reporting, IFRS Convergenc, Transparency.